Sistem Pakar Diagnosa Penyakit Tanaman Padi Menggunakan Metode Forward Chaining (Studi Kasus: Kec. Pasar Kemis) - Suwely Suwely; Galuh Saputri (Institut Sains dan Teknologi Nasional, 2023)
Abstract Rice is an important food crop, both for the economy and for meeting the basic needs of society. As the population of Indonesia increases, the need for food also continues to increase. Pasar Kemis whose residents are farmers. Researchers use a research method by other researchers in system development is to use the forward chaining method. Pasar Kemis sub-district has many diseases in their rice plants such as stem rot, tungro, and fusarium diseases. So that farmers deal with their rice diseases with more accurate solutions. So that when planting rice, farmers fail to harvest or the rice yields do not match what they expected, so this system is needed for consulting farmers. The result of this design is an expert system on rice plants, where the system can check for diseases and receive diagnostic results about rice plant diseases. Keywords: Expert System, Forward Chaining, Rice Plants